A Broadband Linear-to-Circular Transmission Polarizer Based on Right-Angled Frequency Selective Surfaces. (27th December 2017) - Zhang, Wei; Li, Jian-ying; Xie, Jian
Abstract : A broadband linear-to-circular transmission polarizer using a right-angled frequency selective surface is presented in this paper. The new proposed polarizer has both advantages of wide operational bandwidth and high transmission coefficients. To verify the design, a new polarizer working in X-band is optimized and fabricated. Experimental results show that the measured axial ratios lower than 3 dB range from 6.42 to 13.70 GHz, with low insertion loss. Meanwhile, the polarizer can operate over a broad range of frequencies from 6.75 to 10.75 GHz, when the incident angle increases to 25°.